IMPLEMENTASI MATRIKS IMPORTANCE PERFORMANCE ANALYSIS (IPA) UNTUK MENGEMBANGKAN KEWIRAUSAHAAN MAHASISWA FAKULTAS EKONOMI DAN BISNIS UNIVERSITAS PANCASILA - Erwin Permana; Supriadi Thalib; Harimurthi Wulandjani (Fakultas Ekonomi Dan Bisnis Universitas Pancasila, 2022)
The existence of entrepreneurs in a country is very strategic in order to create new jobs, absorb labor, and encourage independence in the community. The greater the number of business actors in a country, the stronger the country's economy. So every effort that leads to the formation of an entrepreneurial culture, especially on campus, needs to be encouraged. This study aims to (1). analyzing the development of student entrepreneurship activities at FEB UP, (2) Analyzing entrepreneurship courses from aspects of teaching materials, learning methods and targets for entrepreneurship lectures in fostering the entrepreneurial spirit of FEB UP students, and (3) How is the potential for entrepreneurship development among FEB UP students. Research respondents are FEB UP students who have taken entrepreneurship courses, the number of samples obtained is 140 students. Data analysis using Importance Performance Analysis Matrix. The results showed that in general, the quality of the implementation of entrepreneurship courses was considered quite good by students. The development of coaching activities at the Faculty of Economics and Business, Pancasila University is quite encouraging. The potential for developing an entrepreneurial spirit among FEB students at Pancasila University is very large, this can be seen from the results of research showing the increasing interest of students to consider entrepreneurship as a career choice after graduating from college, the more research and community service to develop the entrepreneurial spirit and the more many seminars, scientific discussions, and entrepreneurship-oriented student activities. To improve the entrepreneurial culture on campus, it is recommended to improve the implementation of the Entrepreneurship Court lectures by conducting lectures every semester. The entrepreneurial concept that has been produced by students must be supported by the entrepreneurial infrastructure on campus and provide support for investment cooperation from the campus to student businesses that are already running.